Spatial pattern and influencing factors of urban elderly meal assistance facilities: a case study from Beijing, China, based on multi-source data - Tuke Zheng; Xidong Ma; Xiaoqing Cheng (Journal of Asian Architecture and Building Engineering)
Meal assistance service is vital for promoting community-based services for the elderly, ensuring the health and well-being of older adults. Taking Beijing, China, as a study area, this paper applied geospatial and statistical methods to examine the spatial pattern and influencing factors for three types of meal assistance facility (MAF) (Type A: MAF of elderly care facilities; Type B: MAF of community dining tables; Type C: MAF of corporate contracting) based on multi-source data. The results showed that: 1) 47.91% of MAFs were located in six central urban districts, with Type A dominating (73.41%), while suburban distribution remained sparse and uneven; 2) MAF development surged after 2015, with 84.63% established thereafter, showing an outward expansion from city center; 3) Subway station accessibility was a positive factor across all types (mean β = 0.124), with additional factors for each type: Type A was further influenced by elderly population density (β = 0.464), neighborhood (β = 0.233), and healthcare (β = 0.094); Type B by elderly population density (β = 0.181) and office space (β = 0.076); Type C by neighborhood (β = 0.259) and GDP (β = 0.127) (all p < 0.01). These insights can offer guidance for future MAF planning.